Can my robotic home cleaner be happy? Issues about emotional expression in non-bio-inspired robots. (October 2016) - Bonarini, Andrea
In many robotic applications, a robot body should have a functional shape that cannot include bio-inspired elements, but it would still be important that the robot can express emotions, moods, or a character, to make it acceptable, and to involve its users. Dynamic signals from movement can be exploited to provide this expression while the robot is acting to perform its task. A research effort has been started to find general emotion expression models for actions that could be applied to any kind of robot to obtain believable and easily detectable emotional expressions. The need for a unified representation of emotional expression emerged. A framework to define action characteristics that could be used to represent emotions is proposed in this paper. Guidelines are provided to identify quantitative models and numerical values for parameters, which can be used to design and engineer emotional robot actions. A set of robots having different shapes, movement possibilities, and goals have been implemented following these guidelines. Thanks to the proposed framework, different models to implement emotional expression can now be compared in a sound way. The question mentioned in the title can now be answered in a justified way.